A multi-proxy approach to detect the pore pressure and the origin of overpressure in sedimentary basins: An example from the Gulf of Suez rift basin - Radwan, Ahmed E. (Frontiers in Earth Science, 2022)
The pore pressure gradient and fracture gradient (PPFG) are critical parameters for drilling mud weight design in the energy industry. Successful drilling operations can be achieved successfully through the understanding of the pore pressure and fracture pressure in the subsurface succession. The scope of this research is to use an integrated approach that encompasses well-logging, basin modeling, drilling-based interpretations, and reservoir measurement methods to gain a reasonable PPFG model and decrease the drilling uncertainties in the El Morgan oil field in the Gulf of Suez. Moreover, it investigates the overpressure generation mechanisms in the basin, which have not been studied before in this area. In this work, PPFGs of more than 16 km of cumulative thick sedimentary succession were modeled and evaluated using an integrated approach. This study utilizes Eaton’s sonic and resistivity-based methods for pore pressure evaluation, while vertical stress was calculated based on the composite density profile. The study revealed that the top geo-pressure was detected at a depth of 1,030 m of Tortonian sediments. Late Miocene sediments reveal hard over-pressure with a maximum gradient of 0.55 PSI/feet, while Middle Miocene sediments exhibit mildly over-pressured, normal, and sub-normal pore pressure zones. The lowest pore pressure values were measured in the Langhian-Serravalian Kareem reservoir with a gradient of 0.29 PSI/feet. With the exception of a slight difference in the reservoir section, the pore pressure profiles in the northern and southern parts of the El Morgan oil field are relatively similar. Reservoir connectivity is believed to be the main reason behind pore pressure magnitude differentiation in the Middle Miocene reservoirs. The key mechanism for generating overpressure has been identified as disequilibrium compaction, and reservoir overcharging may contribute as an excess-pressure generation mechanism at the reservoir level. The presented approach can be applied in PPFG studies for both development and exploratory geomechanical studies in other areas of the Gulf of Suez basin or elsewhere in the world.